The vanishing of ethnos and new forms of struggle for identity: the Eastern Romance inhabitants of Istria - Nowicka, Ewa (Balcanica Posnaniensia. Acta et studia, 2022)
The paper is based on the results of two anthropological researches conducted within the communities living in the Istria Peninsula. Until recently they have used specific local Eastern Romance dialects. The text is dedicated to the process of violent changes which endangered the existence of this population in the context of its language and identity. The described groups are being assimilated and integrated to the Croatian-speaking majority and Croatian national culture. On the base of interviews with representatives of local communities from Žejane and Šušnjevica the historical traditions, social status of these groups and the character of their relations with neighbouring population will be described. Moreover, social and educational activities towards the cultural revival of these communities, taken by the local intelligentsia, will be discussed.